Non Performing Financing dan Strategi Penanganannya pada Akad Murabahah di KSPPS Risalatuna Berkah Sejahtera - Andika, Arif; Afriyanti, Afriyanti; Ulyadi, Ulyadi; Muslim, Mulyadi (Risalah Iqtishadiyah, 2025)
Problematic financing is referred to as Non-Performing Financing (NPF), which includes financing with delinquent collectability and financing with doubtful collectability that has the potential to become delinquent. This study aims to examine the factors causing Non-Performing Financing and the handling strategies for Murabaha contracts at KSPPS Risalatuna Berkah Sejahtera. To achieve the objectives of this research, the author employs a descriptive qualitative research method. The data collection techniques used are documentation studies and in-depth interviews. In terms of problematic financing, KSPPS Risalatuna Berkah Sejahtera has been ineffective due to factors such as the lockdown during the COVID-19 pandemic and natural disasters, which resulted in an uncertain income for the customers. The strategies for handling Non-Performing Financing implemented by KSPPS Risalatuna Berkah Sejahtera include reducing installments, meaning providing long-term settlement time, and lowering profits by using collateral. KSPPS Risalatuna Berkah Sejahtera also seeks to resolve problematic financing through social funds and penalty funds from other customers; however, this is often not done in a timely manner.